Developing creative product designs inspired by ethnic cultural heritage : A case study of design students at the University of Botswana - Setlhatlhanyo, Keiphe Nani; Marope, Odireleng; Moalosi, Richie; Sealetsa, Oanthata Jester (FormAkademisk, 2019)
Due to colonisation and globalisation, ethnic cultures are changing and Botswana’s ethnic cultures are no exception to this change. This study aims to explore how the ethnic culture of different tribes in Botswana can be used to inspire the design of new products. A case study was conducted with students at the University of Botswana on particular themes of ethnic cultural knowledge, which inspired them to design futuristic innovative products. Visual analysis was used to assess the student designs for how they informed current trends without distorting their ethnic cultural meaning. The findings indicated that students were able to design using their own cultural heritage, to work in teams, thus, attaining soft skills, and to modernise ethnic cultural symbols to design symbolic, innovative, and futuristic products.